Doing 'dirty work': Stigma and esteem in the private security industry. (May 2016) - Hansen Löfstrand, Cecilia; Loftus, Bethan; Loader, Ian
This article draws upon two different ethnographic studies – one based in Sweden, the other in the United Kingdom – to explore how private security officers working in a stigmatized industry construct and repair their self-esteem. Whereas the concept of 'dirty work' (Hughes, 1951) has been applied to public police officers, an examination of private security officers as dirty workers remains undeveloped. Along with describing instances of taint designation and management, we find that the occupational culture of security officers enhances self-esteem by infusing security work with a sense of purpose. As members of a tainted occupation, security officers employ a range of strategies to deflect scorn and reframe their work as important and necessary.